Information System in Enhancing Managerial Competencies: An Organisational Perspective - Das, Pradip Kumar (International Journal of Computer Sciences and Engineering, 2015)
Information system in organisation better known as Management information system (MIS) deals with improving the performance of organizations and people through the use of information technology. The four distinct components of MIS are: information strategy, information technology strategy, information management strategy, and change Management/ implementation strategy. This paper focuses on management information system competencies and strategies. The specific fields in which MIS has become invaluable like Strategy Support, Data Processing. MIS resources can be divided into three broad categories: human, technological, and relationship resources. Consistent with the importance of intangible resources, the paper focuses on the intangible dimensions of these three resources. Specifically, it includes MIS human capital, IT infrastructure flexibility, and MIS partnership quality and shows how each of these resources will have a direct positive relationship with MIS competencies. Secondly, competencies are socially complex routines that determine the efficiency with which organizations transform inputs into outputs. MIS competencies can be divided into three categories—foundation competencies, management competencies and portfolio competencies. Thirdly, MIS strategy is a plan for developing management information systems, which maximize the ability of the organization to achieve its agreed objectives. A strategy providing the framework for the organization for ensuring competencies between systems, prioritizing development, and encouraging the elimination of redundant systems is suggested in the paper.